1985
DOI: 10.1007/bf00333427
|View full text |Cite
|
Sign up to set email alerts
|

Accidental exposure to sarin: vision effects

Abstract: Two men were accidentally exposed to vapors of sarin, a cholinesterase inhibitor and extremely toxic nerve gas. Diagnosis was confirmed by depressed cholinesterase activity, and fixed extremely miotic pupils. No other signs or symptoms developed and neither man required treatment. Recovery to normal cholinesterase activity was gradual over a 90-day period. Pupillary reflexes were not detectable until 11 days after exposure; the miotic pupils dilated slowly over a 30-45 day-period. Eye pain and blurred vision d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 8 publications
0
30
0
Order By: Relevance
“…[84][85][86] ). Median lethal concentration and time (LCt 50 ) in rats for sarin is 150 mg/m 3 for ten minutes lasting inhalation 87 . The toxicity of nerve agents is much more apparent than standard pesticides: e.g.…”
Section: Fig 2 Inhibition Of Ache By Nerve Agent Sarin (Reaction 1)mentioning
confidence: 99%
“…[84][85][86] ). Median lethal concentration and time (LCt 50 ) in rats for sarin is 150 mg/m 3 for ten minutes lasting inhalation 87 . The toxicity of nerve agents is much more apparent than standard pesticides: e.g.…”
Section: Fig 2 Inhibition Of Ache By Nerve Agent Sarin (Reaction 1)mentioning
confidence: 99%
“…5,500 passengers, subway workers, rescue staff and police officers were exposed and 12 died 3) . In addition to research on the mechanisms of acute sarin poisoning [4][5][6][7][8] , various studies have elucidated the chronic effects of sarin poisoning [9][10][11][12][13][14][15][16][17] . For example, chronic effects on memory function have been suggested by previous studies which have demonstrated disorders in the central nervous system o f s u b j e c t s e x p o s e d t o s a r i n b y a b n o r m a l electroencephalograms 9,10) or abnormal evoked potentials 11) .…”
mentioning
confidence: 99%
“…The consequences of respiratory failure is systemic hypotension, pulmonary hypertension, polycythaemia, tachycardia and cerebral dysfunction ranging from confusion and coma [12][13][14].…”
Section: Discussionmentioning
confidence: 99%